(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2013)
Managing a business has never been easy. Trying economic conditions make it even harder. The challenge is to do more with less and to make better decisions for the growth of the modern business. Having immediate access to current, actionable information can make a huge difference. “Business Intelligence therefore refers to a set of tools and techniques that enable a company to transform its business data into timely and accurate information for the decisional process, to be made available to the right persons in the most suitable form.” Business Intelligence systems help the users make the right decisions based on the available data. Over the last few years the pressure has been growing to manage, integrate, analyse and act on increasing amounts of information from all kinds of data sources. Business Intelligence is not a new idea. The largest and best managed organizations in the world have been making use of it for more than a decade. Along the way, the giants that pioneered BI made an important discovery –the path to true business intelligence passes through a Data Warehouse. With these modern Data Warehouse Architectures flexibility and responsiveness is greatly improved while minimising the total cost of ownership. “A data warehouse is a subject-oriented, integrated, time variant and non-volatile collection of data in support of management decision making process.” A data warehouse is a relational database that is designed for query and analysis rather than for transaction processing. Modern Businesses today are not only demanding analysis of data from its own operational systems but also the ability to consume, filter and analyse data from a broad range of external data sources. Business intelligence systems provide the ability to answer these critical questions by turning the massive amount of data from operational systems into a format that is current, actionable, and easy to understand. THE DESIGN OF ADATAWAREHOUSE INVOLVES 1) Acquisition of data for the warehouse. 2) Ensuring that Data Storage meets the query requirements efficiently. 3) Giving full consideration to the environment in which the data warehouse resides. Both quality and consistency of data are major concerns. There are many different issues faced in the implementation of a Data Warehouse, its Architecture and Design. So, this paper highlights the need of Data Warehousing in the modern business strategies, features of data warehouse, the different issues faced in the implementation of the data warehouse and different concerns of the data warehouse architecture and design. It also discusses the solution to these issues along with the research and case studies that are documented in this field.